Aspetti del rapporto del giovane Heidegger con la Erkenntnistheorie e la Wertphilosophie di Rickert - Cantillo, Giuseppe (Bollettino Filosofico, 2020)
This essay aims to define the young Heidegger’s relationship with Heinrich Rickert’s philosophy by carrying out an analysis of his 1916 published essay Die Zeitbegriff in der Geschichtwissenschaft, inspired by a confrontation with Rickert’s problem of natural and scientific knowledge and its limits, as well as with the methodological and philosophical determination of “historical science”. The essay carries out an analytical recognition of references made about Rickert within Habilitationschrift of 1916 (Die Kategorien-und Bedeutungslehre des Duns Scoto) and finally it takes cognizance of a critical comparison with transcendental philosophy of values throughout the Summer Term 1919 lectures focused on Rickert (Phänomenologie und transzendentale Weltphilosophie). Therefore, early Heidegger’a writings may be said to link up through an opening up of the philosophical perspective towards and past critical confines of the theory of knowledge and on to a radical philosophy capable of insight and affording a vision of the authentic origins of spiritual life. Keywords: Heidegger, History, Rickert, Theory of Knowledge, Values